An A1-type granite that borders A2-type: insights from the geochemical characteristics of the Zongyang A-type granite in the Lower Yangtze River Belt, China. Issue 17 (21st November 2020) - Jiang, Xiao-Yan; Wu, Kai; Luo, Jin-Cheng; Zhang, Li-Peng; Sun, Wei Dong; Xia, Xiao-Ping
ABSTRACT: Mesozoic A-type granites are widely distributed in the Lower Yangtze River Belt (LYRB) in China, but their petrogenesis and geodynamic settings are unresolved. Here, we describe geochronological and geochemical study of granites from the Zongyang area of the LYRB. Zircon LA-ICPMS U-Pb dating indicates the granites were emplaced at ca. 127 Ma. They have geochemical characteristics similar to those of A-type granites, with high total-alkali (10.5–10.7 wt.%), HFSEs (Zr + Nb + Ce + Y = 890–1011 ppm), high Ga/Al ratios (10, 000 × Ga/Al = 3.19–3.25), and high whole-rock zircon saturation temperatures (850°C–900°C). In discrimination diagrams, samples plot in the A1 -type granite field but close to the A1 –A2 boundary. A representative whole-rock sample yielded an I Sr ratio of 0.7066 and an εNd (t) value of – 5.3, with zircon εHf (t) and δ 18 O values of – 0.2 to – 4.3 and 5.95‰–6.79‰, respectively, all higher than those of depleted mantle, indicating the enriched nature of source materials. Apatites in the granite display mantle-origin characteristics. Incompatible element ratios (Y/Nb, Y/Ta, Nb/U and Ce/Pb) also support the enriched mantle source, and suggest that the source had experienced metasomatism, or the existence of crustal input during magmatic processes. Significant depletions in Ba, Sr, P, Ti, and Eu in the granites indicate fractional crystallization of feldspar and some accessory minerals. We conclude that the Zongyang granite were formed through fractional crystallization of oceanic island basalt (OIB)-like basic magmas derived from the lithospheric mantle. They are classified as A1 but their borderline A2 nature is most likely due to metasomatism by slab-derived fluids or melts, possibly involving crustal materials. Our results, together with those of previous studies, indicate that LYRB A-type granites, are the products of partial melting of the mantle or lower continental crust in an extensional setting, caused by slab rollback during the subduction of the Paleo-Pacific Plate.